Assessing the effect of modified Mediterranean‐ketogenic diet on mild cognitive impairment patients through plasma neuron‐derived exosomes. (31st December 2021) - Kumar, Ashish; Sharma, Mitu; Singh, Sangeeta; Su, Yixin; Hsu, Fang‐Chi; Craft, Suzanne; Deep, Gagan
Abstract: Background: Recently, we compared the effect of a high‐fat and low‐carb Modified Mediterranean‐Ketogenic Diet (MMKD) and a low‐fat American Heart Association Diet (AHAD) on 11 cognitively normal (CN) and 9 with mild cognitive impairment (MCI) older adults as a suggestive preventative intervention for Alzheimer's disease (AD). We reported the promising effect of the MMKD on MCI patients as it was well‐tolerated and associated with increased cerebrospinal fluid (CSF) Aβ1‐42, decreased tau, and increased cerebral perfusion. Here, we characterized the plasma neuron‐derived exosomes (NDE) to further understand the molecular mechanisms underlying the efficacy of the MMKD against MCI. Method: The completed study consisted of a randomized crossover design in which participants (both CN and MCI) consumed either the MMKD or the control AHAD for six weeks. Total exosomes (TE) were isolated from plasma by precipitation method, and NDE were enriched using Biotin‐tagged CD171 antibody attached with streptavidin‐magnetic beads. The purity, concentration, and size of TE and NDE were assessed by flow cytometry, nanoparticle tracking, immunogold‐labeling, electron microscopy, and exosome antibody array. NDE was characterized for several AD and neurodegeneration‐related biomarkers, advanced glycation endproducts (AGEs), glutamate, glutamate receptors, and β‐hydroxybutyrate (BHB) by ELISA and colorimetric assays. NDE effect on NF‐kB activity in human monocytes was studied as a molecular surrogate for inflammation. Result: We confirmed the size, shape, and purity of both TE and NDE by multiple methods. Importantly, the MMKD treatment strongly reduced the level of Aβ1‐42 (by 50%, p=0.001), p(181)Tau (by 17%), and neurofilament L (by 55%, p=0.03) in the MCI group, but not with AHAD. MMKD reduced the AGEs in both CN and MCI groups and strongly increased the glutamate level in NDEs from the MCI group (6 fold, p<0.001) but did not affect glutamate in CSF. The MMKD also modulated the expression of various glutamate receptors (GRIN1, GRIA1, GRIN2A, and GRIN2b). Interestingly, we detected BHB in NDEs, though no significant change was observed. MMKD inhibited the NF‐κB activity in monocytes suggesting a strong anti‐inflammatory effect. Conclusion: NDE offers a promising peripheral measure to assess the efficacy and molecular mechanism of MMKD action against MCI.